If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(3x + 2) = 12x + 8 Reorder the terms: 9(2 + 3x) = 12x + 8 (2 * 9 + 3x * 9) = 12x + 8 (18 + 27x) = 12x + 8 Reorder the terms: 18 + 27x = 8 + 12x Solving 18 + 27x = 8 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 18 + 27x + -12x = 8 + 12x + -12x Combine like terms: 27x + -12x = 15x 18 + 15x = 8 + 12x + -12x Combine like terms: 12x + -12x = 0 18 + 15x = 8 + 0 18 + 15x = 8 Add '-18' to each side of the equation. 18 + -18 + 15x = 8 + -18 Combine like terms: 18 + -18 = 0 0 + 15x = 8 + -18 15x = 8 + -18 Combine like terms: 8 + -18 = -10 15x = -10 Divide each side by '15'. x = -0.6666666667 Simplifying x = -0.6666666667
| -97-24+130= | | 1/5x+2=16 | | 1.8/0.09 | | 8+n=100 | | 8-n=100 | | 3X+12-4=20 | | 81-9v^2=0 | | (3/4x+6)(-3x+1/2)=0 | | x*5+52=x*8-14 | | y+11=10/11(x-1) | | 8x-15=4+2x | | 7-7x=97-28x | | 6z-5z=7-20 | | 2v*4y^8*3v^5y^6= | | 1-11/2n=100 | | 12x^5y^3*2xy= | | 2x+14=-63-9x | | 5=3(x-0) | | 3(4x+3)(2x-5)=0 | | d-4(d+8)=-8 | | 3(4x-3)(2x-5)=0 | | 8/x=7/x-2 | | 35Q^2+33q+4=0 | | 13(x-9)=7x-10 | | 139=x+2x+(x+15) | | 11(x-2)=7x-11 | | 12x+13=7x+20 | | 32=x+x+(x+2)+(x+2) | | 50x^2-18x+6=0 | | 50x^2-18+6=0 | | 4xy+xy= | | 0.36(6)+0.06x=0.18(6+x) |